PENGARUH CORPORATE BRANDING TERHADAP KEPUTUSAN PEMBELIAN DENGAN EKUITAS MEREK SEBAGAI VARIABEL MEDIASI PADA RUMAH SAKIT IBU DAN ANAK KOTA BANDA ACEH - Farid Farid; Syarifah Faridha (Departemen Manajemen, Universitas Syiah Kuala, 2017)
ABSTRACTThis aims of this study are to investigate the effect of corporate branding, and brand equity on purchase decision The patien of rumah sakit ibu dan anak in Banda Aceh is a taken as a sample in this study. The method of this study employed questionnairs as an instrument. Total sampling is applied as the study’s convenience technique. Hierarchical Linear Modelling methods of analysis are used to determine the influence of the variables involved. The results of this study indicate that corporate branding have positive effect on purchase decision, corporate branding have positive influence on brand equity and brand equity have positive effect on purchase decision. This study also shows that corporate branding influential significantly against brand equity nor against purchase decision. In addition abtained results that brand equity has partial mediated the effect of corporate branding effect to purchase decision. Keywords: Corporate Branding, Brand Equity, Purchase Decision